Effectiveness of art therapy methods on tooth brushing behaviour of preschool children in Padang City: Efektivitas metode art therapy terhadap perilaku menyikat gigi dari anak usia prasekolah di Kota Padang - Ricky Amran; Hanim Khalida Zia; Miratin Khairiah (Makassar Dental Journal, 2024)
The preschool age group is vulnerable to caries problems because children at that age are not yet able to brush their teeth effectively and appropriately. One of the effective learning methods applied to children is art therapy because it makes it easier for them to explore something new and forms a learning environment that makes them happy. Pre-experimental research through time series design used 37 samples achieved through purposive sampling. Data were collected by giving toothbrush cards to students of Fadhilah Amal 3 Kindergarten in Padang City. The results of this study showed different and meaningful results (p=0.00) between the respondents' behaviour before and after the application of art therapy method of giving colour to the picture. It is concluded that art therapy is effective to support tooth brushing behaviour in pre-school children at Fadhilah Amal 3 Kindergarten in Padang City.